Rancang Bangun Aplikasi Monitoring Pelanggaran Siswa di SMK Muhammadiyah 1 Sragen - Cahyaningrum, Endri; , Hernawan Sulistiyanto S.T.,M.T (2016)
Monitoring is a form of control to an object, monitoring management sector in education is a form of supervision of the quality of education manjemen. At SMK Muhammadiyah 1 Sragen there is counseling which has the role of monitoring the personality and behavior of students in the school environment, and to develop the potential of students of counseling. The amount of data used to determine student progress learners and data processing that still manual start student data and data breach so it takes time to analyze student data breach, as well as frequent errors in the student data reporting violations. Application monitoring violations of the student is expected to assist in monitoring violations of the student. Counseling teachers can easily analyze and determine student progress from a data breach. In addition, students can also access this information as a material system introspection students to do better again. The information systems using web-based application which can later be easier for teachers and students in terms of monitoring the violation. Applications designed consists of several pages, including the login page, student data, data breach, input student data, input data breach, and print the letter.